Monte Carlo investigation for an Ising model with competitive magnetic interactions in the dominant ferromagnetic-interaction regime - Nguyen, Oanh K. T.; Nguyen, Phong H.; Nguyen, Niem T.; Bach , Cong T.; Nguyen , Huy D.; Bach, Giang H. (Communications in Physics, 2023)
We apply classical Monte Carlo simulation to examine the thermodynamic properties of perovskites described by the Ising model with competitive magnetic interactions. By correspondingly adjusting the ferromagnetic-interaction and antiferromagnetic-interaction probabilities, \(p\) and \((1-p)\), in the regime \(p \ge 0.5\), the temperature dependence of magnetization, total energy, spin susceptibility, and specific heat consistently show a ferromagnetic to paramagnetic (FM-PM) phase transition at a critical temperature \(T_c\). Besides, the inverse susceptibility is confirmed to follow Curie-Weiss's law above another critical temperature \(T_{CW}\). By increasing the FM interaction probability, we have observed the FM-PM critical temperature \(T_c\) shifted to the higher value while the Curie-Weiss critical temperature \(T_{CW}\) moves to the lower. The different values between these two critical temperatures imply the inhomogeneity of the systems having phase separation, thus in agreement with the increased homogeneity with increasing \(p\).